2016
DOI: 10.5433/1679-0359.2016v37n1p507
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Salminus brasiliensis wild populations in downstream and upstream Cachoeira Branca, Verde River MS Brazil: a preliminary view

Abstract: Although hydroelectric power plants generate most electricity in Brazil, the dams provide environmental barriers which also include the interruption of fish migration. Current study, conducted prior to the construction of São Domingos HPP on the shaft of the Cachoeira Branca (waterfall) on the Verde river, state of Mato Grosso do Sul, Brazil, evaluated the genetic diversity of two natural populations of dourado (Salminus brasiliensis) located downstream (Population A -PopA) and upstream (Population B -PopB) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Indeed, four different genetic lineages of S. hilarii are known in South America (Machado et al, ). Similarly, Ribeiro et al () also pointed out a strong pattern of genetic differentiation between populations of S. brasiliensis downstream and upstream of a natural barrier. The effects of artificial barriers on genetic structure of fish populations in the Neotropical region have been reported for migratory species other than Salminus (Garcez, Calcagnotto, & Almeida‐Toledo, ; Sekine, Prioli, Prioli, & Júlio, ).…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, four different genetic lineages of S. hilarii are known in South America (Machado et al, ). Similarly, Ribeiro et al () also pointed out a strong pattern of genetic differentiation between populations of S. brasiliensis downstream and upstream of a natural barrier. The effects of artificial barriers on genetic structure of fish populations in the Neotropical region have been reported for migratory species other than Salminus (Garcez, Calcagnotto, & Almeida‐Toledo, ; Sekine, Prioli, Prioli, & Júlio, ).…”
Section: Discussionmentioning
confidence: 85%
“…The use of molecular markers to assess the genetic composition of fish populations is an important strategy for measuring the genetic variability among specimens. Recent studies have shown that the use of RAPD (Random Amplified Polymorphic DNA) and microsatellites may provide important information on population genetics in fish culture stations and in natural environments, and these markers are widely used for analysis of genetic variability in several species (Ashikaga et al, 2015;Ribeiro et al, 2016;Coimbra et al, 2017;Souza et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the fragmentation of rivers by the presence of dams may have negative effects on the genetic structure of Brazilian migratory fish populations (RAMOS et al, 2012;ASHIKAGA et al, 2015;RIBEIRO et al, 2016). However, notably, this is not the only factor that endangers the populations of these fishes, as they may also be affected by overfishing, pollution, river banks deforestation, and habitat destruction, among others (LOPERA-BARRERO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%